2022
DOI: 10.1371/journal.pone.0271551
|View full text |Cite
|
Sign up to set email alerts
|

The socio-economic and health effects of COVID-19 among rural and urban-slum dwellers in Ghana: A mixed methods approach

Abstract: Background Vulnerable populations such as rural and urban-slum dwellers are more likely to suffer greatly from the deleterious effects of the novel Coronavirus disease 2019 (COVID-19). However, in Ghana, most COVID-19 mitigating packages are not focused on vulnerable populations. Methods Concurrent mixed methods design was used to examine the socio-economic and health effects of COVID-19 among rural and urban-slum dwellers in Ghana. Four hundred respondents were sampled for the quantitative arm of the study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Earlier studies in two other districts in Ghana equally revealed that misconceptions, myths, and lack of trust in the government's efort towards managing the pandemic contributed to poor attitudes towards COVID-19 prevention and management [35,36]. Other studies have noted that the problem of COVID-19 vaccine hesitancy is not limited to the Ghanaian population but to African populations [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in two other districts in Ghana equally revealed that misconceptions, myths, and lack of trust in the government's efort towards managing the pandemic contributed to poor attitudes towards COVID-19 prevention and management [35,36]. Other studies have noted that the problem of COVID-19 vaccine hesitancy is not limited to the Ghanaian population but to African populations [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…As was indicated in some settings in this study, the household was supposed to have at least one tippy tap. A similar approach has also been noted in Ghana [ 22 , 31 ], and these tippy taps have been noted to improve hand washing. While this mitigatory measure is welcome, such vulnerable communities should be considered for the provision of long-term mitigatory measures, as the tippy tap does not carry much water and thus would require frequent refilling.…”
Section: Discussionmentioning
confidence: 67%
“…Those with these resources mentioned that hand hygiene was not a challenge, while the absence of these hand washing facilities, soap and/or sanitizer were cited as barriers to hand hygiene. These environmental determinants have also been noted as barriers to hand washing in Ghana among rural and urban slum dwellers [ 22 , 31 ], among slum dwellers in Kenya [ 32 ], young adult students in Canada [ 27 ] and in poor settlements in Accra and Johannesburg [ 33 ]. A previous study in Zimbabwe also identified a lack of hand hygiene facilities as one of the challenges driving SARS-CoV-2 transmission in the country [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Options usually available to informal settlers, especially in Madina, Ghana, is to resort to self-medication and the services of lay health personnel. Similarly, Aberese-Ako et al (2022) also found that during the pandemic informal settlers were afraid to visit health facilities to seek health care because of the misapprehension that coughing, even without a COVID-19 test, might be credited to the COVID-19 disease. These resulted in increase in self-medication.…”
Section: Health-care Systems and Covid-19 In Informal Settlementsmentioning
confidence: 97%